2010
DOI: 10.1111/j.1468-1331.2010.03010.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance spectroscopic imaging in Parkinson’s disease, progressive supranuclear palsy and multiple system atrophy

Abstract: Our findings support the notion that MRSI can potentially quantify basal ganglia cellular pathology in MSA and PSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…A recent study, using a 1.5 T scanner, confirmed the hypothesis that NAA concentrations in the basal ganglia in MSA and PSP would show differences compared with PD, specifically in the pallidum, putamen and lentiform nucleus. These findings support the hypothesis that MRS can potentially quantify basal ganglia cellular pathology in MSA and PSP and differentiate these diseases from PD (Guevara et al, 2010). Moreover, another study demonstrated a reduced NAA/Cr ratio in the putamen that correlated well with the severity of parkinsonism and it was remarked that 1 H MRS may also be useful in monitoring patients with various types of parkinsonism (Abe et al, 2000).…”
Section: Magnetic Resonance Spectroscopysupporting
confidence: 65%
“…A recent study, using a 1.5 T scanner, confirmed the hypothesis that NAA concentrations in the basal ganglia in MSA and PSP would show differences compared with PD, specifically in the pallidum, putamen and lentiform nucleus. These findings support the hypothesis that MRS can potentially quantify basal ganglia cellular pathology in MSA and PSP and differentiate these diseases from PD (Guevara et al, 2010). Moreover, another study demonstrated a reduced NAA/Cr ratio in the putamen that correlated well with the severity of parkinsonism and it was remarked that 1 H MRS may also be useful in monitoring patients with various types of parkinsonism (Abe et al, 2000).…”
Section: Magnetic Resonance Spectroscopysupporting
confidence: 65%
“…A decrease of this ratio indicates neuronal or axonal dysfunction (Firbank et al 2002; Schocke et al 2003; Seppi and Schocke 2005; Hotter et al 2009; Rizzo et al 2016b). MRSI is an advanced 1H-MRS technique, which acquires spectra simultaneously over a large brain region from multiple voxels during the same sequence allowing not only the spatial location of the voxels to be changed (without loss of quality) by sub-voxel shifts during post-processing, but allowing also individual voxels to be aligned with anatomical features and allowing an absolute quantification of metabolites such as NAA to be performed (Guevara et al 2010). As the most commonly used standards (Cr and Cho) seem to vary in concentration, quantitative analysis techniques show advantages compared with alternative ratio-based methods (Esterhammer et al 2010).…”
Section: Techniquesmentioning
confidence: 99%
“…108 Other studies found NAA-Cr to be significantly reduced in the substantia nigra, 109,110 most likely as a sign of neuronal loss. This is also true for other neurodegenerative disorders, such as multisystem atrophy and progressive nuclear palsy, 111 where NAA was found to be significantly decreased in the pallidum, putamen, and lentiform nucleus of these patients. Mapping glutamate and glutamine in the lentiform nuclei demonstrated reduced levels, suggesting that more than half of the dopaminergic neurons in the nigrostriatal projection must be lost before the onset of PD.…”
Section: Parkinson Diseasementioning
confidence: 79%